A Novel Approach for Testing Benchmark Functions using Biogeography based Optimization (BBO) Algorithm - T R, Kalaiarasan; Anandkumar, V.; Kumar A M, Ratheesh; Keerthika, T. (International Journal of Engineering and Technology, 2018)
Biogeography is the science and study of geographical distribution of biological organisms. BBO is a traditional algorithm that maximises efficiency, based on the mathematical aspects of biogeography. The project aims at sharing the probable features between solutions and fitness values that are represented as immigration and emigration between islands. BBO is similar to biological optimization methods i.e. Genetic Algorithm (GA) and Particle Swarm Optimization (PSO) that carries features which are unique. The proposed algorithm of BBO provides a solution to many that uses GA and PSO. This paper demonstrates a performance of the proposed BBO with a set of well known standard benchmark functions.Â Â